Early hemostatic responses to trauma identified with hierarchical clustering analysis - White, N. J.; Contaifer, D.; Martin, E. J.; Newton, J. C.; Mohammed, B. M.; Bostic, J. L.; Brophy, G. M.; Spiess, B. D.; Pusateri, A. E.; Ward, K. R.; Brophy, D. F. (Journal of thrombosis and haemostasis, 2015)
Summary Background Trauma‐induced coagulopathy is a complex multifactorial hemostatic response that is poorly understood. Objectives To identify distinct hemostatic responses to trauma and identify key components of the hemostatic system that vary between responses. Patients/Methods A cross‐sectional observational study of adult trauma patients at an urban level I trauma center emergency department was performed. Hierarchical clustering analysis was used to identify distinct clusters of similar subjects according to vital signs, injury/shock severity, and comprehensive assessment of coagulation, clot formation, platelet function, and thrombin generation. Results Among 84 total trauma patients included in the model, three distinct trauma clusters were identified. Cluster 1 (N = 57) showed platelet activation, preserved peak thrombin generation, plasma coagulation dysfunction, a moderately decreased fibrinogen concentration and normal clot formation relative to healthy controls. Cluster 2 (N = 18) showed platelet activation, preserved peak thrombin generation, and a preserved fibrinogen concentration with normal clot formation. Cluster 3 (N = 9) was the most severely injured and shocked, and showed a strong inflammatory and bleeding phenotype. Platelet dysfunction, thrombin inhibition, plasma coagulation dysfunction and a decreased fibrinogen concentration were present in this cluster. Fibrinolytic activation was present in all clusters, but was particularly increased in cluster 3. Trauma clusters were most noticeably different in their relative fibrinogen concentration, peak thrombin generation, and platelet‐induced clot contraction. Conclusions Hierarchical clustering analysis identified three distinct hemostatic responses to trauma. Further insights into the underlying hemostatic mechanisms responsible for these responses are needed.